Knowledge and Attitude on STDs and HIV and AIDS among Secondary School Students (Shiksha Shastra Saurabh, 2018)
The study was carried out to find out the knowledge and attitude on STDs and HIV and AIDS among Secondary School students of Kathmandu District. This study followed the simple random sampling method to select the respondents. Altogether 120adolescents were the respondents of the study and questionnaire and attitude scale were the tools of the study. The study found that, 25 percent answered full form of STDs and HIV and AIDS correctly. Almost 50 percent of the respondents had knowledge about commercial sex workers who had high risk of STDs and HIV transmission. Similarly, 62.5 percent respondents who answered sex education is needed and same percent expressed condom is on of the most important devices that protect STDs and HIV and AIDS transmission. Premarital and extra marital sex may cause STDs and HIV and AIDS was responded as 25.00, 23.33, 18.33, 30.00 and 3.33 percent as strongly agreed, agreed, undecided, disagreed and strongly disagreed respectively. In the statement ‘students must get proper sexual and reproductive health from junior to higher education’ to prevent and control HIV and AIDS and other STDs and 30.00, 23.33, 15.00, 8.33 and 23.33 percent respondents agreed, undecided, disagreed and strongly disagreed respectively. It seems that respondents were deprived to get proper knowledge on STDs and HIV and AIDS. Hence, government must monitor schools whether they are providing SRH properly or not and also government must appoint the concern academic background HPE Ed. teacher to teach SRH matter properly.